Analysis of Factors that Influence Purchase Intention in the Online Environment - Jevin Tan; Hendrawan Hendrawan; Jhon Indexon; Jihadhatul Akbar (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
Tokopedia is an application that is popular now. Apart from offering many high-quality and economical products, this application can also make it easier for people to purchase goods without having to go out of the house. This research is focused to find out the effect of price, promotion, and product quality on people's decisions in purchasing products in Tokopedia. The sample used for this research is the people in Batam City. The method used is multiple regression analysis using IBM SPSS Statistics 24, based on 370 respondents gathered using a disproportionate random sampling method. The application we use for this research is IBM SPSS Statistics 24. we get in reading and analysis the hypothesis are that there is a significant effect between price, promotion, and product quality on product purchasing decisions in the Tokopedia.